POLITIK HUKUM PIDANA TERHADAP KEBIJAKAN KRIMINALISASI DAN DEKRIMINALISASI DALAM SISTEM HUKUM INDONESIA - Situmeang, Sahat Maruli Tua (Res Nullius Law Journal, 2022)
Criminalization is one of the central problems of criminal law policy. Based on the description of the background above, the problems that arise are, first, how is the legal politics regarding criminalization and decriminalization in the Indonesian legal system, and second, how is the regulation of criminalization and decriminalization in the Indonesian legal system in the future. The approach method used in this research is a normative juridical approach. Based on the results of the study, it shows that the criminal law system as a form of political embodiment of criminal law should be formed with the spirit of the 1945 Constitution as a juridical basis. Consequently, the criminal law system must be spelled out concretely in every statutory regulation. Therefore, criminal law must be truly aspirational to the needs of the wider community, both in terms of legal certainty, justice and expediency. However, with the size and punishment guidelines not yet fully regulated, it has the potential to cause criminogenic factors and over-criminalization. In connection with the regulation of criminalization and decriminalization in the legal system in the future, which is with the dynamic nature of the law, where the law must follow developments in society. Therefore, it is necessary to synchronize and harmonize laws and regulations as well as a judicial review mechanism as an effort to decriminalize. Based on this, criminal policy through non-penal efforts should be prioritized.